2016
DOI: 10.1093/cid/ciw719
|View full text |Cite
|
Sign up to set email alerts
|

Azithromycin 1.5g Over 5 Days Compared to 1g Single Dose in Urethral Mycoplasma genitalium : Impact on Treatment Outcome and Resistance

Abstract: Extended azithromycin 1.5g was no more effective than a single 1g dose at achieving cure of M. genitalium urethritis and importantly did not reduce the selection of macrolide resistance. Nonmacrolide and new approaches for the treatment of M. genitalium urethritis are required.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
74
1
6

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(85 citation statements)
references
References 21 publications
4
74
1
6
Order By: Relevance
“…This study provides only moderate evidence that fewer patients with MG urogenital infection will fail treatment and develop macrolide resistance with the extended 5-day regimen compared with azithromycin 1 g which conflicts with the recent findings of Read et al 30. Caution needs to be continued to be exercised when using the extended regimen as a replacement for azithromycin 1 g and all patients followed up to establish that they have been cured as some patients will still fail treatment either due to pre-existent macrolide resistance or to its emergence following treatment and may be asymptomatic 1–3 25.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…This study provides only moderate evidence that fewer patients with MG urogenital infection will fail treatment and develop macrolide resistance with the extended 5-day regimen compared with azithromycin 1 g which conflicts with the recent findings of Read et al 30. Caution needs to be continued to be exercised when using the extended regimen as a replacement for azithromycin 1 g and all patients followed up to establish that they have been cured as some patients will still fail treatment either due to pre-existent macrolide resistance or to its emergence following treatment and may be asymptomatic 1–3 25.…”
Section: Discussioncontrasting
confidence: 99%
“…Finally, an alternative but not mutually exclusive explanation is that in populations with high level of resistance mixed infections, not detected with the current methodologies, would tend to contribute to apparent resistance development. Taken together, the conclusion of Read et al that the extended azithromycin 1.5 g was no more effective than a single 1 g dose should be viewed with caution and highlights the need for further high-quality prospective studies using this regimen 30. When the data from the Read study is added to this study and combined in a crude way, no difference is observed between azithromycin 1 g and the extended regimen in post-treatment macrolide mutations (p=0.09) but remains significantly different when patients with prior doxycycline are included (p=0.005).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…genitalium and macrolide testing in asymptomatic patients. The data presented indicate that 63.1% of the specimens had macrolide resistance-associated mutations; however, these single nucleotide mutations confer high-level resistance to azithromycin and have been consistently associated with clinical failure of this drug (10, 24). Comparison to phenotypic resistance assay results was not possible in this study due to the well-established difficulty in culturing M.…”
Section: Resultsmentioning
confidence: 91%
“…The men carried a wild-type organism before treatment, but their post-treatment specimens contained mutations in the 23S rRNA gene that conferred macrolide resistance [18]. Since then, other investigators have also detected macrolide resistance mutations de novo (also known as acquired, induced or selected) in M. genitalium [7,10,[19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%